1997
DOI: 10.1021/es960937t
|View full text |Cite
|
Sign up to set email alerts
|

A Fast Method for Recycling Fly Ash:  Microwave-Assisted Zeolite Synthesis

Abstract: Zeolitic material was synthesized from fly ash by conventional and microwave-assisted hydrothermal alkaline activation experiments. The zeolite synthesis was studied as a function of temperature, time, and activation solution concentration. K+-Na+/NH4 + exchange properties of the zeolitic material synthesized were studied as a function of time and zeolite type. The zeolitic material synthesized from the same fly ash by changing the synthesis parameters contained:  NaP1, hydroxysodalite, hydroxycancrinite, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
16

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 245 publications
(115 citation statements)
references
References 19 publications
1
96
0
16
Order By: Relevance
“…Although there has been no report on the CEC of FA-derived linde F zeolite, Querol et al reported that 23.1 mg g -1 (1.4 meq g -1 ) of ammonium (NH4 + ) ions was adsorbed on the FA-derived linde F zeolite. 6) Further study is needed in order to elucidate the adsorption of various harmful ions on linde F zeolite.…”
Section: Jcs-japanmentioning
confidence: 99%
“…Although there has been no report on the CEC of FA-derived linde F zeolite, Querol et al reported that 23.1 mg g -1 (1.4 meq g -1 ) of ammonium (NH4 + ) ions was adsorbed on the FA-derived linde F zeolite. 6) Further study is needed in order to elucidate the adsorption of various harmful ions on linde F zeolite.…”
Section: Jcs-japanmentioning
confidence: 99%
“…The zeolitization of CFA by microwave heating has also been reported to be useful for shortening the reaction time. 66) Microwaves are absorbed directly by water as the solvent, which enables more rapid heating than by conventional heating processes. The electromagnetic waves induce water dipole rotation, probably activating water molecules by the breaking of hydrogen bonds.…”
Section: )mentioning
confidence: 99%
“…Synthesis of zeolites from coal fly ash is one of the promising applications of fly ashes with high added value [9]. Since the initial studies of zeolite synthesis from fly ash by Höller and Wirsching (1985) [10], various methods and patents have been proposed, improved and applied by many authors to synthesize different types of zeolites , among which direct conversion is a common synthesis method [19,[22][23][24][25]. Due to the peculiar structural properties of zeolites, they have a wide range of industrial applications, such as ion exchange, and gas and water adsorption, among others [35,36].…”
Section: Introductionmentioning
confidence: 99%